2021
DOI: 10.3390/ijms221910416
|View full text |Cite
|
Sign up to set email alerts
|

Defective Lysosomal Lipolysis Causes Prenatal Lipid Accumulation and Exacerbates Immediately after Birth

Abstract: Cholesterol and fatty acids are essential lipids that are critical for membrane biosynthesis and fetal organ development. Cholesteryl esters (CE) are degraded by hormone-sensitive lipase (HSL) in the cytosol and by lysosomal acid lipase (LAL) in the lysosome. Impaired LAL or HSL activity causes rare pathologies in humans, with HSL deficiency presenting less severe clinical manifestations. The infantile form of LAL deficiency, a lysosomal lipid storage disorder, leads to premature death. However, the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…Biochemical quantification of lipids showed a tendency toward elevated TG levels in HF/HCD without GDM and significantly increased TG concentrations (2.1-fold) in placentae of GDM dams, whereas total cholesterol (TC) and CE concentrations were not affected ( Figure 2 B). In line with results from our previous study [ 17 ], the most abundant lipid in the placenta was cholesterol, more specifically FC ( Figure 2 B). Increased placental lipid levels prompted us to further examine the occurrence and activities of intracellular lipases.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Biochemical quantification of lipids showed a tendency toward elevated TG levels in HF/HCD without GDM and significantly increased TG concentrations (2.1-fold) in placentae of GDM dams, whereas total cholesterol (TC) and CE concentrations were not affected ( Figure 2 B). In line with results from our previous study [ 17 ], the most abundant lipid in the placenta was cholesterol, more specifically FC ( Figure 2 B). Increased placental lipid levels prompted us to further examine the occurrence and activities of intracellular lipases.…”
Section: Resultssupporting
confidence: 92%
“…Unexpectedly, we observed increased neutral and acid CE hydrolysis, in line with transcriptional upregulation of the respective lipid hydrolases, suggesting increased CE turnover in HF/HCD and GDM placentae. The enzymes responsible for placental CE hydrolysis are LAL at acidic pH and HSL at neutral pH, the only known CE-degrading lipases expressed and active in the mouse placenta [ 17 ]. Increased acid TG lipase activity observed in the present study confirms previous data from streptozotocin-injected rats and diabetic humans [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral (pH 7) and acid (pH 4.5) CEH and TGH activities were measured in cell and tissue lysates by using radioactively labeled substrates as described previously [ 42 ] with minor modifications. Briefly, tissues and cells were lysed in neutral lysis buffer (100 mM potassium phosphate, 1 mM dithiothreitol (Carl Roth, Karlsruhe, Germany), pH 7), sonicated twice on ice for 10 s, and centrifuged at 1,000× g and 4 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a study investigated the effect of genetic disruption of murine LAL and demonstrated CE accumulation in placentae and fetuses, suggesting that lysosomal rather than neutral lipolysis already alters placental and fetal cholesterol homeostasis in utero . Furthermore, LAL deficiency led to massive hepatic lysosomal lipid accumulation after birth, with a severe progression in young adulthood [ 71 ]. The insight that aberrant LAL expression leads to a severe metabolic disorder not only during pregnancy but also in the first weeks of life in mice underlines the crucial role of this hydrolase in lysosomal CE metabolism.…”
Section: Hydrolase Types and Implications In Placental Biologymentioning
confidence: 99%